Dietary Patterns Measured by Principal Component Analysis and its Association with Stunting among Nepalese Schoolchildren in Nepal - Shrestha, A.; Shrestha, A.; Cissé, G. (Kathmandu University Medical Journal, 2021)
Background There is a gap of knowledge on the link of major dietary patterns with stunting among schoolchildren in Nepal. Objective To identify dietary patterns in rural Nepalese households in two districts and assess their association with stunting among schoolchildren. Method This cross-sectional study gathered data from 708 schoolchildren aged 8-16 years participating in the baseline survey in the Districts of Dolakha and Ramechhap, Nepal. We derived major dietary patterns from a principal component analysis of reported intake from a food frequency questionnaire completed through interviews with the caregivers. Statistical analysis was conducted using mixed logistic regression with random intercepts at the level of schools adjusting for socio-demographic and behavioural indicators. Result The diet of surveyed schoolchildren was mainly comprised of starchy staples and legumes. Five dietary patterns score were derived: mixed food, vegetables and lentils, milk and beverages, salty snacks, and processed food. The vegetables and lentils pattern scores were negatively associated with stunting (aOR 0.84; 95% CI: 0.66-1.08, p=0.17) after adjusting for regional differences, demographic and behavioural risk factors. Conclusion Our results suggest that adherence to dietary patterns high in vegetables and animal protein might be associated with reduced odds of being stunted among schoolchildren. Therefore, the promotion of dietary diversification strategies to improve schoolchildren’s food consumption is required in the study area.